2012
DOI: 10.4415/ann_12_03_09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and lifestyle of patients with amyotrophic lateral sclerosis in Campania: brief overview of an Italian database

Abstract: Abstract. Background. Physical activity and occupational exposures appeared to play a relevant role in pathogenesis of amyotrophic lateral sclerosis (ALS), a neurodegenerative disease of unknown origin. Materials and methods. We aimed to make an overview of the clinical characteristics and lifestyle (occupation and sport) of a population of 395 patients with ALS from campania, in southern Italy. Results. ALS onset resulted anticipated of about 11 years in industry workers, whilst the more frequent site of onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Physical activity is an important determinant of metabolic homeostasis and hence may be very relevant to ALS risk. Several studies, in fact, report that high levels of physical activity and/or an athletic lifestyle significantly increase the risk and/or worsen the prognosis of ALS [ 11 , 25 , 72 , 98 , 123 , 169 ]. However, not all studies have come to this conclusion [ 173 , 177 ], and one study suggests that exercise and high levels of physical activity may even be beneficial, with overall physical activity associated with a reduced odds (OR = 0.56, 95% CI: 0.36–0.87) of having ALS [ 138 ].…”
Section: The Disease-modifying Effects Of Metabolic Disorders In Alsmentioning
confidence: 99%
“…Physical activity is an important determinant of metabolic homeostasis and hence may be very relevant to ALS risk. Several studies, in fact, report that high levels of physical activity and/or an athletic lifestyle significantly increase the risk and/or worsen the prognosis of ALS [ 11 , 25 , 72 , 98 , 123 , 169 ]. However, not all studies have come to this conclusion [ 173 , 177 ], and one study suggests that exercise and high levels of physical activity may even be beneficial, with overall physical activity associated with a reduced odds (OR = 0.56, 95% CI: 0.36–0.87) of having ALS [ 138 ].…”
Section: The Disease-modifying Effects Of Metabolic Disorders In Alsmentioning
confidence: 99%
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that L-BMAA is most likely to be implicated, the questionnaire also covers items already described in the literature such as dwelling location (urban/rural), occupation, presence of certain industries in the dwelling environment, toxic exposure during employment or hobbies, participation in sport, physical trauma, alcohol and tobacco consumption 23 26 32 33 48 128–131. As there is probably a long latency period between exposure and appearance of ALS132 133 and given that L-BMAA exists in a protein-associated form which could act as an endogenous neurotoxic reservoir over time,55 an in-depth study will involve gathering details of dwelling since birth (in order to collect their precise residential history), and for other items from age 13.…”
Section: Methods and Analysismentioning
confidence: 99%